2017
DOI: 10.3389/fonc.2017.00172
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Multiple Draining Lymph Node Basins in Melanoma: A Matched-Pair Analysis Based on the John Wayne Cancer Institute Experience

Abstract: BackgroundThe prognostic significance of multiple draining basins is controversial in melanoma because analyses have not adequately controlled for standard prognostic variables. We hypothesized that an analysis based on prognostically matched pairs of patients with multiple versus single drainage basins would clarify any independent role of basin number.Study designWe identified patients in our 40-year prospective database, who underwent preoperative lymphoscintigraphy, intraoperative sentinel node biopsy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…1 Several studies have since refuted Sappey's work by showing cutaneous malignancies with multiple lymphatic basin drainage (MLBD) patterns, some crossing the midline. [2][3][4][5][6][7][8][9] Although MLBD is commonly seen in primary truncal melanomas, the occurrence of SLN metastasis in multiple lymphatic basins is not common. We report a case of synchronous positive bilateral axillary SLN metastasis in a patient with primary cutaneous melanoma on the posterior trunk and review what is known about SLNs in melanoma patients with MLBD.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several studies have since refuted Sappey's work by showing cutaneous malignancies with multiple lymphatic basin drainage (MLBD) patterns, some crossing the midline. [2][3][4][5][6][7][8][9] Although MLBD is commonly seen in primary truncal melanomas, the occurrence of SLN metastasis in multiple lymphatic basins is not common. We report a case of synchronous positive bilateral axillary SLN metastasis in a patient with primary cutaneous melanoma on the posterior trunk and review what is known about SLNs in melanoma patients with MLBD.…”
Section: Introductionmentioning
confidence: 99%
“…As lesões primárias que levaram à indicação de BLNS localizavam-se no tronco (26), membros inferiores (14), membros superiores (6) e cabeça e pescoço (2) (Tabela 1). A linfocintilografia pré-operatória permitiu a identificação da da base de drenagem linfonodal (BDL) em todos, exceto um paciente.…”
Section: Resultsunclassified
“…Entre os pares combinados, a BDL múltipla não afetou as taxas de sobrevida global de metástases LN, recorrência geral, recorrência loco-regional ou recorrência à distância. [26][27][28] Complicações A BLNS é um procedimento invasivo e não isento de riscos. Complicações e sequelas são muito menos comuns quando comparadas à dissecção completa de LN.…”
Section: Cadeias De Drenagemunclassified
“…In cutaneous melanoma, the prognostic significance of multiple drainage basins is still unclear [ 61 ]. As recommended, SLNB is performed for each basin identified during lymphoscintigraphy [ 62 ].…”
Section: Predictive and Prognostic Factors Of Lymphoscintigraphy For mentioning
confidence: 99%
“…The results showed that the number of drainage basins did not affect rates of SLN metastasis, OS, DSS, overall recurrence, locoregional recurrence, and distant recurrence. In conclusion, this study demonstrated that as identified by lymphoscintigraphy multiple basin drainage is not an independent biological or prognostic factor in primary cutaneous melanoma [ 61 ].…”
Section: Predictive and Prognostic Factors Of Lymphoscintigraphy For mentioning
confidence: 99%